Dangerous sex, invisible labour: sex work and the law in India - Kotiswaran, Prabha (New Delhi, 2012)
Popular representations of third-world sex workers as sex slaves and vectors of HIV have spawned abolitionist legal reforms that are harmful and ineffective, and public health initiatives that provide only marginal protection of sex workers' rights. In this book, Prabha Kotiswaran asks how we might understand sex workers' demands that they be treated as workers. She contemplates questions of redistribution through law within the sex industry by examining the political economies and legal ethnographies of two archetypical urban sex markets in India-Sonagachi in Kolkata and Tirupati in Andhra Pradesh. Providing new insights into the lives of these women-many of whom are demanding the respect and legal protection that other workers get-she builds a persuasive theoretical case for recognizing these women's sexual labor. Moving beyond standard feminist discourse on prostitution, Kotiswaran draws on a critical genealogy of materialist feminism for its sophisticated vocabulary of female reproductive and sexual labor, and uses a legal realist approach to show why criminalization cannot succeed amid the informal social networks and economic structures of sex markets. Based on this, she assesses the law's redistributive potential by analysing the possible economic consequences of partial decriminalization, complete decriminalization, and legalization. Kotiswaran concludes with a theory of sex work from a postcolonial materialist feminist perspective.
Keywords: Sexual labour-India